2019
DOI: 10.1242/dev.180398
|View full text |Cite
|
Sign up to set email alerts
|

A cellular atlas of Pitx2-dependent cardiac development

Abstract: The Pitx2 gene encodes a homeobox transcription factor that is required for mammalian development. Disruption of PITX2 expression in humans causes congenital heart diseases and is associated with atrial fibrillation; however, the cellular and molecular processes dictated by Pitx2 during cardiac ontogeny remain unclear. To characterize the role of Pitx2 during murine heart development we sequenced over 75,000 single cardiac cell transcriptomes between two key developmental timepoints in control and Pitx2 null e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 46 publications
(62 reference statements)
4
39
0
Order By: Relevance
“…Our results also confirm recent data from mouse atria indicating that cardiomyocytes are the major cell type expressing PITX2 in the adult left atrium ( 36 ). Furthermore, we found that approximately one-quarter of nuclei in human left atrium are cardiomyocyte, consistent with prior data in mice ( 36 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also confirm recent data from mouse atria indicating that cardiomyocytes are the major cell type expressing PITX2 in the adult left atrium ( 36 ). Furthermore, we found that approximately one-quarter of nuclei in human left atrium are cardiomyocyte, consistent with prior data in mice ( 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our results provide the first evidence to our knowledge that low left atrial cardiomyocyte PITX2 levels contribute to recurrent AF after ablation in patients in whom left atrial tissue was collected at the time of AF ablation. Our results also confirm recent data from mouse atria indicating that cardiomyocytes are the major cell type expressing PITX2 in the adult left atrium (36). Furthermore, we found that approximately one-quarter of nuclei in human left atrium are cardiomyocyte, consistent with prior data in mice (36).…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 92%
See 2 more Smart Citations
“…Putting these ideas into play, the research papers in this Special Issue demonstrate a range of single cell techniques and the discoveries that they enable. Two papers apply live imaging to demonstrate the role of a signal transduction pathway in differentiation (Deathridge et al, 2019) or to demonstrate stochasticity in fate choice (Antolovićet al, 2019); several papers build transcriptomic maps of specific developing tissues that will prove useful resources and reveal new hypotheses for developmental regulation (Combes et al, 2019;Martin et al, 2019;Hulin et al, 2019;Li et al, 2019a,b); several studies computationally reconstruct developmental dynamics (Bastidas-Ponce et al, 2019;Delile et al, 2019;Guo and Li, 2019;Prior et al, 2019;van Gurp et al, 2019); and one study benchmarks in vitro differentiation to in vivo development and develops new computational tools to do so (Edri et al, 2019). Taking a slightly different approach, other papers use single cell analyses to characterize cell behaviors during morphogenesis (Amini et al, 2019;Yang et al, 2019), to investigate how cells respond to DNA or tissue damage (Miermont et al, 2019;Dell'Orso et al, 2019), and to understand how heterogeneities in gene and protein concentration influence development (Papadopoulos et al, 2019;Reznik et al, 2019;Velte et al, 2019).…”
mentioning
confidence: 99%